Administration of three autochthonous Bacillus subtilis strains induce early appearance of gastric glands and vestiges of pylorus in Piaractus mesopotamicus larvae - Guidoli, Marcos Gabriel (2016)
Autochthonous microorganisms as probiotics are a novel alternative to antibiotics. The genus Bacillus is highly used by its ability to survive on adverse conditions. Piaractus mesopotamicus, a native fish, is the most producedspecie in Argentinian aquaculture. The low level of knowledge, high stress conditions and demand of animals led to a deficit in the number of larvae and fry. The aim of this study was to evaluate the probiotic effect of previously selected autochthonous Bacillus on biometrical parameters of P. mesopotamicus larvae when administered together in a combined suspension in different doses and stages. Results showed that the bacterial administration did not causesignificant effects on the variables evaluated. However, the dose containing 6 × 107 CFU L-1 of each strain showed the highest average values of P. mesopotamicus biological parameters, regardless the stage of administration.Histological evaluations of animals administered with this dose did not showed adverse effects and indicated the capability of this dose, administered in a particularly period of time, to stimulate the early appearance of gastricglands, vestiges of what would be the pylorus and a higher development of liver. Thus, we proposed the safe use ofthis dose in a combined probiotic mixture to be studied in further assays.